Nano-enhanced cooling techniques for photovoltaic panels: A systematic review and prospect recommendations. (October 2021) - Kandeal, A.W.; Algazzar, Almoataz M.; Elkadeem, M.R.; Thakur, Amrit Kumar; Abdelaziz, Gamal B.; El-Said, Emad M.S.; Elsaid, Ashraf Mimi; An, Meng; Kandel, Reham; Fawzy, Hossam Eldin; Sharshir, Swellam W.
Highlights: A comprehensive review of the recent nano-based PV cooling systems is conducted. Separate nano-enhanced PCMs, separate nanofluid-based, and hybrid PV cooling units are discussed. Governing equations of materials' properties and PV performance are derived. Detailed systems' description and major results are illustrated. Research trend is analyzed via VOSviewer software based on Scopus database, and Future prospects are suggested. Abstract: The environmental pollution and growing energy demand necessitate the development of power generation using renewable energy systems, especially solar photovoltaic (PV) panels. Despite being an eco-friendly and durable power generation technology, PVs demerit for low conversion efficiency (15–20%). In other meaning, a very low amount of the incident irradiance is converted into electricity, whereas the major is absorbed as heat, uplifting the PVs' surface temperature and declining their efficiency and reliability. Therefore, it is crucial to find a proper cooling technique for upgrading PVs' performance. Recently, along with the nanotechnology development, nano-based PV cooling units have been proposed and investigated as the inclusion of nanoparticles enhances the thermal properties of base materials. Herein, in this paper, the conducted efforts to improve the PVs' performance using nano-based cooing systems were reviewed and discussed. The surveyed PVs' cooling methodologies were classified into separate and hybrid systems: nano-enhanced PCMs, nanofluid-based, and hybrid nano-based cooling units. All relevant equations of materials' properties and PV performance were presented. In addition, the research trend of this field was analyzed by conducting a comprehensive bibliometric analysis using VOSviewer software and based on the Scopus database in the period (2006–2020). Besides, comprehensive discussions of proposed and designed systems were conducted, and major findings were summarized. Based on the literature, using hybrid nano-based cooling systems, the surface temperature reduction can reach 16 °C with enhancement in electrical efficiency up to 50% compared to conventional uncooled PV panels. Furthermore, some future work suggestions were given.